Artificial Intelligence Based Identification and Monitoring of Student Using OpenCV - Mangal, Mayank; Pandey, Adarsh; Wagh, Jayesh; Gaonkar, Sahil; Bhanushali, Jagruti (2024 International Conference on Advances in Computing Research on Science Engineering and Technology (ACROSET), 2024)
Nowadays, Artificial Intelligence plays a very crucial role in IT as well as Management sector. People are very busy and unproductive when it comes to handle huge terabytes of data. Tracking of candidate work in institution and organization can increase a productivity as well as the project completion ontime. One of the parts of tracking system we are introducing in picture is Attendance Monitoring and Identification of student or employee at the same time by using the OpenCV libraries. Ability to compute the attendance percentage as well as the introduce in the form of graphical representation is the most efficient way to come up. This project is nothing but the model or the software system which give solution related Attendance marking as well as admin of all the data related in the candidate to the most secure place and format. Here the GUI is the interface which is provided by developer to the user which having multiple option like to register and image recognition and model training and other admin power. Other than this looking to the task related to the data management and handling we use the database which is access by SQL queries. To retrieve and alter the relevant data in the database, queries are utilized. Using the model, views and controller in the system design, short form of the acronyms is MVC architecture. Application is installing in the organization as well as institution with designated candidate to handle it.